Chlorination of phenylallene derivatives with 1-chloro-1,2-benziodoxol-3-one: synthesis of vicinal-dichlorides and chlorodienes - Zhao, Zhensheng; Murphy, Graham K. (Beilstein Journal of Organic Chemistry, 2018)
Allyl and vinyl chlorides represent important structural motifs in organic chemistry. Herein is described the chemoselective and regioselective reaction of aryl- and α-substituted phenylallenes with the hypervalent iodine (HVI) reagent 1-chloro-1,2-benziodoxol-3-one. The reaction typically results in vicinal dichlorides, except with proton-containing α-alkyl substituents, which instead give chlorinated dienes as the major product. Experimental evidence suggests that a radical mechanism is involved.
Keywords: allene; chlorination; hypervalent iodine; synthetic methods; vinyl chloride

Organic Polymer Chemistry: An Introduction to the Organic Chemistry of Adhesives, Fibres, Paints, Plastics and Rubbers - Saunders, K. J. (Poly(Vinyl Chloride) and Related Polymers, 1988)

(untitled) - Hernandes, M. Z.; Cavalcanti, S. M. T.; Moreira, D. R. M.; Filgueira de Azevedo Junior, W.; Leite, A. C. L. (Curr. Drug Targets, 2010)

(untitled) - Smith, B. R.; Eastman, C. M.; Njardarson, J. T. (J. Med. Chem., 2014)

(untitled) - Jeschke, P. (Pest Manage. Sci., 2010)

(untitled) - Herrera-Rodriguez, L. N.; Khan, F.; Robins, K. T.; Meyer, H. P. (Chim. Oggi, 2011)

Modern Methods in Crop Protection Research - Jeschke, P. (The Unique Role of Halogen Substituents in the Design of Modern Crop Protection Compounds, 2012)

(untitled) - Tang, M. L.; Bao, Z. (Chem. Mater., 2011)

(untitled) - Hiszpanski, A. M.; Saathoff, J. D.; Shaw, L.; Wang, H.; Kraya, L.; Lüttich, F.; Brady, M. A.; Chabinyc, M. L.; Kahn, A.; Clancy, P.; Loo, Y.-L. (Chem. Mater., 2015)

(untitled) - Gribble, G. W. (Environ. Sci. Technol., 1994)

(untitled) - Gribble, G. W. (Heterocycles, 2012)

(untitled) - Wang, B.-G.; Gloer, J. B.; Ji, N.-Y.; Zhao, J.-C. (Chem. Rev., 2013)

(untitled) - Gribble, G. W. (Acc. Chem. Res., 1998)

(untitled) - Wallner, O. A.; Szabó, K. J. (J. Org. Chem., 2003)

(untitled) - Gosmini, C.; Bégouin, J.-M.; Moncomble, A. (Chem. Commun., 2008)

(untitled) - Nakamura, H.; Shim, J.-G.; Yamamoto, Y. (J. Am. Chem. Soc., 1997)

(untitled) - Solin, N.; Narayan, S.; Szabó, K. J. (J. Org. Chem., 2001)

(untitled) - Solin, N.; Narayan, S.; Szabó, K. J. (Org. Lett., 2001)

Palladium Reagents and Catalysts - Tsuji, J. (Pd(0)-Catalyzed Reactions of Allylic Compounds via π-Allylpalladium Complexes, 2005)

(untitled) - Dounay, A. B.; Overman, L. E. (Chem. Rev., 2003)

(untitled) - Barluenga, J.; Fernández, M. A.; Aznar, F.; Valdés, C. (Chem. Commun., 2004)

(untitled) - Reddy, C.; Reddy, V.; Urgaonkar, S.; Verkade, J. G. (Org. Lett., 2005)

(untitled) - Ma, S.; Jiang, X.; Cheng, X.; Hou, H. (Adv. Synth. Catal., 2006)

(untitled) - Lemay, A. B.; Vulic, K. S.; Ogilvie, W. W. (J. Org. Chem., 2006)

(untitled) - Geary, L. M.; Hultin, P. G. (J. Org. Chem., 2010)

(untitled) - Rossi, R.; Bellina, F.; Lessi, M. (Tetrahedron, 2011)

(untitled) - Thakur, A.; Zhang, K.; Louie, J. (Chem. Commun., 2012)

(untitled) - Han, F.-S. (Chem. Soc. Rev., 2013)

(untitled) - Ruiz-Castillo, P.; Buchwald, S. L. (Chem. Rev., 2016)

(untitled) - Boyes, A. L.; Wild, M. (Tetrahedron Lett., 1998)

(untitled) - Laali, K. K.; Nandi, G. C.; Bunge, S. D. (Tetrahedron Lett., 2014)

(untitled) - Bäckvall, J.-E.; Jonasson, C. (Tetrahedron Lett., 1997)

(untitled) - Mueller, W. H.; Butler, P. E.; Griesbaum, K. (J. Org. Chem., 1967)

(untitled) - Poutsma, M. L. (J. Org. Chem., 1968)

(untitled) - Lasne, M. C.; Thuillie, A. (Bull. Soc. Chim. Fr., 1974)

(untitled) - Eisenberger, P.; Gischig, S.; Togni, A. (Chem. – Eur. J., 2006)

(untitled) - Zhu, N.; Wang, F.; Chen, P.; Ye, J.; Liu, G. (Org. Lett., 2015)

(untitled) - Purkait, N.; Okumura, S.; Souto, J. A.; Muñiz, K. (Org. Lett., 2014)

(untitled) - Moriarty, R. M.; Hopkins, T. E.; Vaid, R. K.; Vaid, B. K.; Levy, S. G. (Synthesis, 1992)

(untitled) - Zhao, Z.; Racicot, L.; Murphy, G. K. (Angew. Chem., Int. Ed., 2017)

e-EROS Encyclopedia of Reagents for Organic Synthesis - Knight, D. W.; Russell, G. A. (Phenyliodine(III) Dichloride, 2001)

(untitled) - Xue, C.; Jiang, X.; Fu, C.; Ma, S. (Chem. Commun., 2013)

(untitled) - Egami, H.; Yoneda, T.; Uku, M.; Ide, T.; Kawato, Y.; Hamashima, Y. (J. Org. Chem., 2016)

(untitled) - Wang, M.; Zhang, Y.; Wang, T.; Wang, C.; Xue, D.; Xiao, J. (Org. Lett., 2016)

(untitled) - Yang, X.; She, Y.; Chong, Y.; Zhai, H.; Zhu, H.; Chen, B.; Huang, G.; Yan, R. (Adv. Synth. Catal., 2016)

(untitled) - Parvathaneni, S. P.; Perumgani, P. C. (Asian J. Org. Chem., 2018)

Comprehensive Organic Name Reactions and Reagents - Wang, Z. (Doering-Moore-Skattebøl Reaction, 2010)

(untitled) - Willgerodt, C. (J. Prakt. Chem., 1894)

(untitled) - Keefer, R. M.; Andrews, L. J. (J. Am. Chem. Soc., 1959)

(untitled) - Amey, R. L.; Martin, J. C. (J. Org. Chem., 1979)

(untitled) - Li, X.-Q.; Zhang, C. (Synthesis, 2009)

(untitled) - Tokumura, K.; Ozaki, T.; Nosaka, H.; Saigusa, Y.; Itoh, M. (J. Am. Chem. Soc., 1991)